Auditions set Monday for Children's Theater (Raton, NM Raton Range, 1994)
Article is about auditions for the Missoula Children's Theater production of Cinderella.
Newspaper article + Photograph of local children
Master list item #: 44
File location is in the Raton file Cabinet
Keywords: Missoula Children's Theater -- Children performance group; New Mexico Arts Division -- Sponsor; McCune Foundation -- Sponsor; Santa Fe Pacific Foundation -- Sponsor; Children's Theater; Plays; Live performance; Arts and Humanities Council; Auditions; Shuler Theater; Raton, New Mexico